Latin American NGOs’ perceptions of cross-scale and cross-actor interactions in polycentric climate governance - Tosun, Jale; Levario Saad, Emiliano; Tobin, Paul (Climate & development, 2025)
The governance of climate change has increasingly been characterized as polycentric, with non-state actors playing particularly influential roles as climate intermediaries. Yet, there has been limited empirical analysis of climate intermediaries within polycentric climate governance systems. We examine how Latin American non-governmental organisations experience and navigate polycentric climate governance by analysing their roles as climate intermediaries. Drawing on the Ecology of Games framework, we analysed the experiences of 22 non-governmental organizations across 14 Latin American countries to examine agency within polycentric climate governance systems. Our findings reveal that the organizations perceive themselves as climate intermediaries, connecting diverse actor types including government agencies, international organizations, local communities, and private sector entities across multiple governance scales from local to international levels. In evaluating their relationships with other governance actors, these organisations emphasize three critical dimensions: learning through knowledge exchange and capacity building, coordination through collaborative planning and resource sharing, and equity and fairness in decision-making processes and outcome distribution. These findings enhance our understandings of how Latin American non-governmental organisations experience the polycentric landscape of climate governance, contributing to the transnational advocacy literature while demonstrating the analytical value of the Ecology of Games framework for actor-centred analysis of polycentric climate governance systems.